Developmental lead exposure induces depressive-like behavior in female rats - Lisboa, SFD; Goncalves, G.; Komatsu, F.; Queiroz, CAS; Almeida, A. A.; Moreira, E. G. (Marcel Dekker Inc, 2005)
The involvement of neurotoxicants in the etiology of emotional pathologies is becoming an issue in neurotoxicology. Lead (Pb) exposure during childhood has been associated with increased impulsivity, aggressivity, and delinquency. Considering the paucity of experimental studies investigating the involvement of developmental Pb exposure in emotional disorders, our objective was to investigate whether Pb exposure during pregnancy and/or lactation could be related to depressive symptoms in adult male and female rats. Wistar dams received 10 mg of Pb, as Pb acetate, or 13.4 mg of Na acetate, by gavage, daily, during pregnancy and lactation. By cross-fostering at the time of birth, pups were either exposed to Ph or Na acetate during pregnancy only, lactation only, or during both pregnancy and lactation. At 70 days of age, animals were submitted to the open-field test followed by the forced swimming test. Ph levels were measured in the blood of dams (weaning) and pups (after behavioral evaluation). The results demonstrated that exposure to Ph during both pregnancy and lactation induced, in males, an increased emotionality state detected in the open-field test, and in females, depressive-like behavior detected in the forced swimming test. These alterations were observed at residual blood Pb levels (i.e., around 5 mug/dL).
Keywords: depression; forced swimming test; lead; open-field test